The role of attitudes in perceptions of bicycle facilities: A latent-class regression approach. (February 2021) - Clark, Calvin; Mokhtarian, Patricia L.; Circella, Giovanni; Watkins, Kari
Highlights: Bicycle facilities with greater separation were perceived positively. Those that are more accepting of risks are less impacted by separated facilities than the risk-cautious. Risk tolerance was a better delineator for perceptions of comfort and safety than bike enjoyment. Abstract: While many professionals support bicycling for transportation to reduce traffic congestion and improve public health, many potential cyclists see the risks from traffic injuries as a major barrier. The purpose of this paper is to investigate the impact of bicycle facilities on perceptions of bikeability, and how these perceptions vary among different groups. Data comes from surveys (N = 2157) deployed in ten study neighborhoods as part of two research projects. Respondents were asked to rate a series of images of hypothetical roadways in terms of perceived comfort, perceived safety, and willingness to try bicycling. Latent-class regression was used to model these responses, with bicycle facility type and roadway characteristics as explanatory variables and sociodemographics and attitudinal factors (car preference, bike enjoyment, risk tolerance, and anti-exercise) as covariates for class membership. A recurring theme among the presented solutions is the emergence of two pro-bicycle classes - risk-embracing and risk-cautious - together with a pro-car class. Results indicate that the impact of protected bicycle facilities on perceptions are much higher for the pro-bike/risk-cautious group. The major implication of these findings is that there likely exists a sizeable segment of the population that, although perhaps just as interested in bicycling as the typical pro-bicycle class, is more cautious in their perceptions of comfort and safety. Those belonging to this subgroup generally view minimal facilities as much more unsafe and uncomfortable than their risk-accepting counterparts, but have comparable perceptions regarding high-quality protected bicycle facilities.